Pengaruh Permainan Tradisional Egrang Batok Kelapa Tehadap Peningkatan Kemampuan Motorik Kasar Pada Anak Usia 5-6 Tahun - Putri Anisa Alifiya Rahma; Dita Yuliastrid; Noortje Anita K; Indra Himawan Susanto (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
A child's motor movement is a movement that is carried out with the aim of exemplifying the behavior carried out by every human being. Children's motor skills are influenced by the maturity of the child's nerves and muscles. In other words, it is looked at and adjusted to the child's age and neurological maturity. Motor movements can be carried out if there is coordination of thousands of complex muscles, the movements of these muscles can be carried out deliberately, automatically, quickly and accurately. The aim of this research is to find out how much influence the traditional coconut shell stilt game has on improving gross motor skills in children aged 5-6 years. The research method used was quasi-experimental or pre-experimental research using a quantitative type of experiment. The design of this research is a group pretest-posttest design. This research was conducted at the Baitulmutaqien Tonga Wetan Kindergarten. The practical implementation time in the field is 12 meetings in 6 weeks. The research population was only 19 KB-RA Baitulmutaqien Kindergarten students aged 5 to 6 years. In this study, saturated sampling was used, that is, the entire population was used. The instrument in this research is standing on one leg in a "T" position. The hypothesis testing technique uses the Wilcoxon T test. The research results show that the Sig value (2-tiled) standing on one leg is 0.014 ≤ 0.05. This indicates that providing the traditional sport of coconut shell stilts has a significant influence on improving the gross motor movements of KB-RA Baitul Muttaqien Lidah Wetan Kindergarten students.